Complementary and alternative therapies for restless legs syndrome: An evidence-based systematic review. (April 2018) - Xu, Xiao-Min; Liu, Yang; Jia, Shi-Yu; Dong, Mei-Xue; Cao, Du; Wei, You-Dong
Summary: Restless legs syndrome (RLS) is defined as an irresistible urge to move the legs, which is usually accompanied by paresthesias or dysesthesias at least twice weekly, and affects 2%–4% of adults in Europe and North America. This systematic review assesses the current complementary and alternative options for RLS and the potential benefits of those treatments on sleep quality, mood disorder, and quality of life. A systematic search of the PubMed, Embase, Cochrane, and Web of Science databases was conducted. Eighteen studies met the inclusion criterion, which included the use of the international RLS study group criteria. Complementary and alternative therapies have been found to be effective in both primary and secondary RLS. The severity of primary RLS symptoms can be significantly ameliorated by exercise training, transcutaneous spinal direct current stimulation, pneumatic compression devices, light therapy, repetitive transcranial magnetic stimulation, and acupuncture. Pneumatic compression devices and yoga also improve RLS-related disorders. Exercise training is highly efficacious in the reduction of symptom severity in uremic RLS and related effects such as poor quality of life. Endovenous laser ablation may be a good choice for patients with concurrent RLS and superficial venous insufficiency.